Role of saline infusion sonohysterography in infertility evaluation - Vinita Singh; Byasdev Mishra; Snehil Sinha; Sarita Agrawal; Pushpawati Thakur (Wolters Kluwer Medknow Publications, 2018)
Introduction: Etiology of infertility is multifactorial, and fallopian tube abnormality being one of the most important causes accounts for up to 40% of female subfertility if not less and is further increasing. Saline infusion sonohysterography (SIS) procedure is gaining popularity and is being widely practiced and accepted as a screening tool in assessing tubal patency in infertile patients attending infertility clinic and has become popular as a routine test for the evaluation of the uterine cavity in the investigation of infertility and abnormal uterine bleeding. Objective: To compare the results of SIS with that of hysterosalpingography in infertility evaluation and to observe the role of SIS to find out endometrial pathology and tubal patency in infertility patients. Materials and Methods: A retrospective, observational study was done on the basis of record maintained in the ultrasound register and case record sheets of all infertile women who underwent infertility treatment and fulfilled the inclusion criteria from June 2015 to August 2016. Results: SIS had sensitivity of 91%, specificity of 76% positive predictive value (PPV) of 95%, negative predictive value (NPV) of 66%, and accuracy of 89% of SIS in evaluating tubal patency. Further, SIS showed sensitivity of 83.3%, specificity of 60%, PPV of 75%, NPV of 75%, and accuracy of 72% in detecting pelvic pathology. Conclusion: In a low-resource country like India where patients are also less educated, SIS can prove to be a useful tool in initial workup of infertility patients with better compliance, low cost, and better results in a single visit.